Prognostic Role of S100A8 and S100A9 Protein Expressions in Non-small Cell Carcinoma of the Lung - Hyun Min Koh; Hyo Jung An; Gyung Hyuck Ko; Jeong Hee Lee; Jong Sil Lee; Dong Chul Kim; Jung Wook Yang; Min Hye Kim; Sung Hwan Kim; Kyung Nyeo Jeon; Gyeong-Won Lee; Se Min Jang; et al. (Journal of Pathology and Translational Medicine, 2019)
Background S100A8 and S100A9 have been gaining recognition for modulating tumor growthand metastasis. This study aimed at evaluating the clinical significance of S100A8 and S100A9 innon-small cell lung cancer (NSCLC). Methods We analyzed the relationship between S100A8and S100A9 expressions, clinicopathological characteristics, and prognostic significance in tumorcells and peritumoral inflammatory cells. Results The positive staining of S100A8 in tumorcells was significantly increased in male (p < .001), smoker (p = .034), surgical method other thanlobectomy (p = .024), squamous cell carcinoma (SQCC) (p < .001) and higher TNM stage (p = .022)compared with female, non-smoker, lobectomy, adenocarcinoma (ADC), and lower stage. Theproportion of tumor cells stained for S100A8 was related to histologic type (p < .001) and patientsex (p = .027). The proportion of inflammatory cells stained for S100A8 was correlated with patientage (p = .022), whereas the proportion of inflammatory cells stained for S100A9 was correlatedwith patient sex (p < .001) and smoking history (p = .031). Moreover, positive staining in tumorcells, more than 50% of the tumor cells stained and less than 30% of the inflammatory cellsstained for S100A8 and S100A9 suggested a tendency towards increased survivability in SQCCbut towards decreased survivability in ADC. Conclusions S100A8 and S100A9 expressions might be potential prognostic markers in patients with NSCLC.